An appraisal to Hans Berger by the time of his 150th birthday: the human EEG and tales of blood flow, heat and brain waves - Caeira, Marlon Wycliff; Caboclo, Luis Otávio; Paola, Luciano de (Arquivos de Neuro-Psiquiatria, 2023)
More than 100 years of research have passed by and still the human electroencephalogram (EEG) remains a puzzle to be solved. Starting from his studies on plethysmography until his theories on brain thermodynamics, Hans Berger was able to refine his method of recording cortical signs with the apparatus at his disposal in an ordinary neuropsychiatric yard towards an early account of human EEG. This review is an appraisal of his contribution to the field of modern neurophysiology.
Keywords: Electroencephalography; History; Brain Waves; Alpha Rhythm